2014
DOI: 10.1051/0004-6361/201424762
|View full text |Cite
|
Sign up to set email alerts
|

The FERRUM project: Experimental transition probabilities from highly excited even 5s levels in Cr ii

Abstract: We report lifetime measurements of the five levels in the 3d 4 (a 5 D)5s e 6 D term in Cr  at an energy around 83 000 cm −1 , and log(g f ) values for 38 transitions from the investigated levels. The lifetimes are obtained using time-resolved, laser-induced fluorescence on ions from a laser-produced plasma. Since the levels have the same parity as the low-lying states directly populated in the plasma, we used a two-photon excitation scheme. This process is greatly facilitated by the presence of the 3d 4 (a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
0
26
1
Order By: Relevance
“…The experimental set-up for single-step experiments at the Lund High Power Laser Facility has recently been described in detail (Engström et al 2014), and here we focus mainly on the new features involved in the two-step process. The experimental set-up is presented in Fig.…”
Section: E X P E R I M E N Tmentioning
confidence: 99%
“…The experimental set-up for single-step experiments at the Lund High Power Laser Facility has recently been described in detail (Engström et al 2014), and here we focus mainly on the new features involved in the two-step process. The experimental set-up is presented in Fig.…”
Section: E X P E R I M E N Tmentioning
confidence: 99%
“…The TR-LIF set-up at Lund High Power Laser Facility is recently described in detail by Engström et al (2014), where a study similar to this, but for Cr , is reported; here we only emphasize the important aspects. The set-up contains two Nd:YAG lasers operating at 10 Hz.…”
Section: Radiative Lifetime Measurementsmentioning
confidence: 90%
“…The experimental set-up for the two-step Time-Resolved Laser Induced Fluorescence (TR-LIF) measurements at the Lund High Power Laser Facility has been described in detail by Engström et al (2014) and Lundberg et al (2016). For an overview, we refer to fig.…”
Section: I F E T I M E M E a S U R E M E N T Smentioning
confidence: 99%